Novel Copper Oxide Bio-Nanocrystals to Target Outer Membrane Lectin of Vancomycin-Resistant Enterococcus faecium (VREfm): In Silico, Bioavailability, Antimicrobial, and Anticancer Potential - Mahmoud Kandeel; Mohamed Sharaf; Arshad Mahdi Hamad; Ahmad O. Babalghith; Mohnad Abdalla; Muhammad Arif; Reem Binsuwaidan; Nashwah G. M. Attallah; Hossam Aladl Aladl Aladl; Samy Selim; Mariusz Jaremko (Molecules, 2022)
In present study, we used Olea europaea leaf extract to biosynthesize in situ Copper Oxide nanocrystals (CuO @OVLe NCs) with powerful antibacterial and anti-cancer capabilities. Physio-chemical analyses, such as UV/Vis, FTIR, XRD, EDX, SEM, and TEM, were applied to characterize CuO @OVLe NCs. The UV/Vis spectrum demonstrated a strong peak at 345 nm. Furthermore, FTIR, XRD, and EDX validated the coating operation’s contact with colloidal CuO @OVLe NCs. According to TEM and SEM analyses, CuO @OVLe NCs exhibited a spherical shape and uniform distribution of size with aggregation, for an average size of ~75 nm. The nanoparticles demonstrated a considerable antibacterial effect against E. faecium bacterial growth, as well as an increased inhibition rate in a dose-dependent manner on the MCF-7, PC3, and HpeG2 cancer cell lines and a decreased inhibition rate on WRL-68. Molecular docking and MD simulation were used to demonstrate the high binding affinity of a ligand (Oleuropein) toward the lectin receptor complex of the outer membrane to vancomycin-resistant E. faecium (VREfm) via amino acids (Leu 195, Thr 288, His 165, and Ser 196). Hence, our results expand the accessibility of OVLe’s bioactive components as a promising natural source for the manufacture of physiologically active components and the creation of green biosynthesis of metal nanocrystals.